Dusun Gubuk Baru Youth Education About the Benefits, Impacts, and Uses of Chemicals - Ricky Arista Pratama; Sulhan Hadi; Adrian Saputra (LPPM Institut Studi Islam Sunan Doe, 2022)
Knowledge of youth chemistry is an important factor in supporting the behavior and treatment of the youth generation for all types of chemicals used in everyday life. Knowledge of youth chemistry can also help families make the best decisions for consumption that suit the needs of parents and children. This scientific writing is the result of the dedication of the Tadris Chemistry Study Program to the Youth of Gubuk Baru Hamlet, Tanak Beak Village, Kec. North Batukliang. The activity aims to increase knowledge about chemistry to the younger generation of Gubuk Baru Hamlet, Tanak Beak Village, Kec. North Batukliang, and its benefits in everyday life. The debriefing materials were provided through relaxed discussions with the youth from Gubuk Baru Hamlet, Tanak Beak Village, Kec. North Batukliang. The method of implementing education about chemistry to youth is interactive lectures, in which interactive dialogue occurs between the resource person and all participants. The youths who attended gave feedback that they were happy to learn chemistry and its benefits in everyday life.